Театр Арбузова - Василинина Ирина Алексеевна (Искусство, 1983)
Экземпляры: КХ (20130121) / Инвентарный номер: 803211 / Цена: 1.30 / Сис.шифр: 85.334.3(2Р=Рус) / Авт.знак: В 19 / ГРНТИ: 18 / ББК: 85.334.3(2Р=Рус)6